PENGARUH PROFITABILITAS TERHADAP LIKUDITAS MELALUI CAPITAL STRUCTURE PERUSAHAAN KOSMETIK Tbk PERIODE 2012-2016 - administrator administrator; Elyda Kurnia Pratiwi; Novrida Qudsi Lutfillah; Muninghar Muninghar (Jurnal Manajerial Bisnis, 2019)
The purpose of this study is to prove and analyze the profitability of liquidity in companies in theIndonesia Stock Exchange for the period 2012-2016. Then to prove and analyze the profitability of thecapital structure of the company on the Indonesia Stock Exchange for the period 2012-2016. Next is toprove and analyze the capital structure of liquidity in companies in the Indonesia Stock Exchange for theperiod 2012-2016. This type of research is quantitative. The population and sample in this study were 6Cosmetic Companies on the Indonesia Stock Exchange for the period 2012-2016. The results in this studyindicate the profitability of the capital structure of companies in the Indonesia Stock Exchange for theperiod 2012-2016; liquidity towards the capital structure of companies in the Indonesia Stock Exchangefor the period 2012-2016; profitability is not towards the attitude of the company on the Indonesia StockExchange for the period 2012-2016.Keywords: profitability, liquidity, capital structure